Hardening of bio-silica in sponge spicules involves an aging process after its enzymatic polycondensation: Evidence for an aquaporin-mediated water absorption - Müller, Werner E.G.; Wang, Xiaohong; Wiens, Matthias; Schloßmacher, Ute; Jochum, Klaus Peter; Schröder, Heinz C. (Biochimica et biophysica acta, 2011)
Spicules, the siliceous skeletal elements of the siliceous sponges, are synthesized enzymatically via silicatein. The product formed, bio-silica, constitutes their inorganic matrix. It remained unexplored which reactions are involved in molding of the amorphous bio-silica and formation of a solid and rigid biomaterial. Cell and molecular biological techniques have been applied to analyze processes resulting in the hardening of the enzymatically synthesized bio-silica. The demosponge Suberites domuncula has been used for the studies. Cell aggregates (primmorphs) from the sponge S. domuncula, grown in the presence of Mn-sulfate, form spicules that comprise, instead of a smooth, a rough and porous surface which is decorated with irregular bio-silica deposits. During this process, the expression of the aquaporin-8 gene becomes down-regulated. Further in vitro studies showed that aquaporin is required for dehydration, and hardening of bio-silica following its enzymatic formation. The data show that in cell aggregates grown in the presence of Mn-sulfate, aquaporin-8 is down-regulated. We conclude that in cell aggregates grown in the presence of Mn-sulfate, the removal of reaction water, produced during the bio-silica polycondensation reaction, is inhibited. This study highlights that besides the silicatein-driven polycondensation reaction, the spicule formation also requires a phase of syneresis that results in a hardening of the material. ► Sponges as a model system for evolution of metazoan body plans. ► Sponges as a model system for basic studies of skeleton formation in animals. ► Enzymatic polycondensation reaction for the formation of bio-silica. ► Expression of aquaporin gene for the first time shown during bio-silica formation. ► First description that bio-silica formation in animals requires a de-hydration step.